IMPLEMENTASI PENCATATAN AKUNTANSI SEDERHANA PADA UMKM DI KABUPATEN TANJUNG JABUNG TIMUR - Siti Fatimah (Journal of Innovative and Creativity, 2026)
Financial record-keeping is an essential element in the management of micro, small, and medium enterprises (MSMEs). However, many MSME actors in Tanjung Jabung Timur Regency have not implemented simple and regular accounting records. This study aims to evaluate the level of implementation of simple financial record-keeping by MSME actors and to identify the challenges they face. The research employs a qualitative approach, using interviews and observations as data collection techniques. The results indicate that most MSME actors have not maintained regular records due to limited knowledge, lack of training, and operational busyness. It is recommended that the local government and MSME support institutions provide practical, hands-on training in simple accounting.